PERTIMBANGAN HAKIM DALAM PUTUSAN NO.10/PID.SUS-TPK/2021/PT.DKI.DIKAITKAN PENERAPAN PASAL 5 UU NOMOR.48 TAHUN 2009: Consideration Judges in Decision No.10/PID.SUS-TPK/2021/PT.DKI.Related of Article 5 of Law No. 48 2009 - Sinaga, Cindy Clarance; Tawang, Dian Adriawan Daeng (Faculty of Law, Universitas Trisakti, 2024)
The consideration of the DKI High Court judge in the Pinangki Malasari case which turned out to be not in accordance with the facts, and not in accordance with the provisions of Article 5 of Law No.48 of 2009. the formulation of the problem of how the judge's consideration in determining the verdict against the suspect in the crime of bribery in a corruption case in decision No. 10/PID.SUS.TPK/2021/PT and how the judge's consideration is related to the provisions in Article 5 of Law No. 48 of 2009. The rresearch method used is normative type, descriptive in nature, the main data is secondary data supported by interviews, how to collect data by literature study and interviews, qualitative analysis and how to draw conclusions using the deductive method. The results and discussion of this study are that judges have not been able to realize a sense of justice in their decisions. The conclusion of the research is that the considerations given by the panel of judges at the appellate level are not in accordance with the fact. Suggestion: The panel of judges in the future in providing consideration matters both mitigating and aggravating must always pay attention to legal principles.